AN ANALYSIS OF DAISY'S AFFAIR IN THE GREAT GATSBY NOVEL BY F.SCOTT FITZGERALD - Novi Sriwulandari; Risma Kartika Dewi; M.Ainul Yaqin; Dewi Chusnul Chotimah (Universitas Islam Lamongan, 2022)
This research is analyzed Daisy's affair in The Great Gatsby novel. It is common that affairs become a problem from the past till nowadays. It is also usually a problem that occurs in married life. Based on the background of the study above, this research focused on answering how is Daisy's affair seen in The Great Gatsby novel and what are the factors that caused Daisy's affair. This study is qualitative research. Therefore, the researcher described Daisy's affair seen in The Great Gatsby novel and also the factors that caused Daisy's affair. The data analysis procedures were based on research findings and discussion, the researcher concluded that Daisy's affair happened involved at least one of the following three elements. They are confidentiality, emotional involvement, and sexual attraction. Besides that Daisy's affair is influenced by several factors there are internal factors that usually appear between spouses and external factors that usually appear from outside their marriage life. In this research, the researcher would like to contribute some suggestions to the next researcher, particularly those who have had the same problem some affairs being a problem from the past until nowadays, especially in marriage life. It is suggested that this study can be a reference for the next researcher.